Razão em forma: Affonso Eduardo Reidy e o espaço arquitetônico moderno - Conduru, Roberto (Risco - Journal of Architecture and Urbanism, 2005)
The text analyses how Affonso Eduardo Reidy explores the plastic possibilities open up by the new means of construction in his projects and built works, as well as in his texts, contributing for the theory and creation of space in archotectonic modernity.